Tindak Pidana Korupsi Dan Pertanggungjawaban Pidana Oleh Korporasi - Fariz Oktan; Artha Febriansyah; Ishandi Saputera (Simbur Cahaya, 2023)
The criminal act of corruption in its development is not only done by human being as legal subject but also corporation as subject of corruption crime. This paper explains how the development of corporations in Indonesia, especially corruption where the corporation can be accounted for by prosecution and sentenced to criminal. And in this paper the author also discusses the theories / doctrines of corporate accountability accompanied by several examples from other countries. But here the author slightly criticize the Judge in Indonesia which in consideration is less clear to use what theory as a basis to sentencing the corporation. So the authors give input for the future in the imposition of criminal, especially against the corporation, Judge included in the consideration of what theory is used in sentencing against the corporation.